Banana Tech- pack 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
It presents the requirements and the complete process for growing bananas. Identifies pests that could affect the crop and the treatment requiret. In addition, it briefly exposes fertilizer options and their recommendations in quantities and treatment follow-up. Finally, it identifies the harvest process in forage conservation, among others. As a final result, the tool complete the process of the crop, which guides the activities with a development of five months and identifies specific comments for each phase of production.